Evaluation of parameters to determine optimum ripeness in Cabernet Sauvignon grapes in relation to wine quality - Botes, Matthys Petrus (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MscAgric (Viticulture and Oenology))--University of Stellenbosch, 2009.